The Influence of Motivation and Job Satisfaction on Employee Performance at the Cooperatives, Small and Medium Enter-prises, Trade and Industry Service of Lamandau Regency - Ernawati Ernawati; Biroum Bernadianto, Raden; Rulinawaty Rulinawaty (International Journal of Economics and Management Research, 2025)
This study aims to analyze the effect of work motivation and job satisfaction on employee performance at the Office of Cooperatives, Small and Medium Enterprises, Trade and Industry of Lamandau Regency. The research method used was a quantitative approach with a questionnaire instrument, involving 40 employees as respondents. The analysis technique applied was multiple linear regression, with the help of SPSS software. The results showed that partially, job satisfaction has no significant effect on employee performance (t count = 0.848; Sig. = 0.402), while work motivation shows a significant effect (t count = 2.204; Sig. = 0.034). However, simultaneously, job satisfaction and work motivation have a significant influence on employee performance (F count = 9.432; Sig. = 0.000). From the results of this study, it is recommended that the Lamandau Regency Office of Cooperatives, Small and Medium Enterprises, Trade and Industry improve factors that can increase employee job satisfaction and motivation to achieve better performance.